Bootstrapping Kelantan and Sarawak Malay dialect models on text and phonetic analyses in text-to-speech system - Khaw, Jasmina Yen Min (2017)
Text-to-speech (TTS) technologies have matured and they have been equipped and embedded in many tools, for instance in mobile phones, robotics and telephony system. For building a TTS system, resources that required are speech corpus, pronunciation dictionary and text. Nevertheless, building an under-resourced Malay dialect TTS system is challenging. The problems of limited language resources in Malay dialects include inexistence of Malay dialects pronunciation dictionaries, quasi-unknown of the sets of Malay dialects phonemes, no standard orthography in Malay dialects and limited written text of Malay dialects.